Children, Youth & Women Organizations in Agriculture Climate Action & Sustainability - Caroo, Keithlin (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Keithlin Caroo, Executive Director at Helen's Daughters, Helen's Daughter - St. Lucia, Mr. Alpha Sennon, Founder of WHYFARM, WhyFarm - Trinidad & Tobago